2024
DOI: 10.18267/j.polek.1413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Political Stability, Geopolitical Risk and R&D Investments on Environmental Sustainability: Evidence from European Countries by Novel Quantile Models

Serpil Kiliç Depren,
Sinan Erdogan,
Mustafa Tevfik Kartal
et al.

Abstract: This research investigates the effect of political stability and geopolitical risk on environmental sustainability (ES) by considering R&D investments in nuclear and renewable energy. Considering the high political stability and recent energy crisis and increasing geopolitical risk, the study focuses on three leading European countries. We use the load capacity factor, include data between 1985/1 and 2020/12, and apply quantile on quantile regression (QQ), Granger causality in quantiles (GQ), and quantile regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The study suggested that promoting renewable R&D and economic expansion encourage green transition as R&D signifi cantly increases green electricity transition (Caglar and Ulug, 2022;Qi et al, 2022). Most of the research conclusions have asserted the importance of R&D in green energy transition; in addition, Kılıç Depren et al (2024) demonstrated in their panel data assessment that improvements in R&D investment strengthen environmental sustainability.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The study suggested that promoting renewable R&D and economic expansion encourage green transition as R&D signifi cantly increases green electricity transition (Caglar and Ulug, 2022;Qi et al, 2022). Most of the research conclusions have asserted the importance of R&D in green energy transition; in addition, Kılıç Depren et al (2024) demonstrated in their panel data assessment that improvements in R&D investment strengthen environmental sustainability.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Natural resource use has tripled in the last forty years. In light of the planet's present limitations, there is an immediate and extensive need to rethink the management of natural resources if we are to achieve global objectives like the SDG, the Paris Climate Agreement, the Aichi targets of the Agreement on Biological Diversity, and the Land Degradation Neutrality of the Convention on preventing Desertification [ 9 ]. The responsible use of natural assets and the development of more environmentally friendly production and consumption practices should be top priorities for all governments.…”
Section: Introductionmentioning
confidence: 99%